AL-TA`RIF WA AL-TANKIR DALAM AL-QURAN (Analisis Terhadap Pemikiran Imam al-Suyuti) - Suhaimi, Suhaimi (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2019)
Uslub or Al-Quran language style is quite varied and all of course contain very poor intention to be understood by all Muslims. However, due to various limitations, so that not all Muslims can know these purposes but by the ulama especially those who are proficient in the fields of Al-Quran sciences including Arabic language. Imam Suyuti is known as one of the scholars who are competent in this matter. He is not only known as an expert on the Qur'an, but also known as a linguist and other sciences. Related to his thoughts on the science of the Koran, in this paper revealed only about one theme that is about ta`rif and tankir or in other terms that are more popular are makrifah and nakirah. Many lafaz in the form of makrifah (definite) and nakirah (indefinite) in the Koran and are often read by us as people who believe in the truth of the holy book, but sometimes we do not think why the lafaz is expressed in this form. Therefore, in this paper an attempt is made to uncover a part of it by raising the thoughts of Imam Suyuti who may increase our insight into the secrets behind the style of the Koran language. In summary, the thought of Imam Suyuti regarding these two terms shows that the use of lafaz in the form of makrifah and nakirah in the Koran has its own purpose or purpose which cannot be exchanged with one another, even though lafaz in general contains the same meaning.